Bed Rest and Intermittent Centrifugation Effects on Human Balance and Neuromotor Reflexes - Paloski, William H; Reschke, Millard F; Feiveson, Alan H (Aerospace medicine and human performance, 2017)
The effects of repeated centrifugation in association with head-down tilt (HDT) bed rest (BR) on the mediation of basic reflexes associated with the major postural muscles was investigated as a potential countermeasure for maintaining balance control and neuromotor reflex function. There were 15 male volunteers who were exposed to 21 d of 6° HDT-BR. Eight were treated with daily 1-h artificial gravity (AG) exposures aboard a short radius centrifuge that provided 1-g footward loading at heart level. The other seven served as HDT-BR control subjects. Balance control was assessed using a standard computerized dynamic posturography (CDP) protocol that was modified by adding low-frequency pitch-plane head movements. Neuromotor reflex function was assessed using tendon stretch reflexes (MSR) and functional stretch reflex (FSR) data collected from the triceps surae muscle group. CDP performance was degraded by HDT-BR in both groups (ranging from 24 to 26%), but was unaffected by AG. BR also degraded MSR and FSR functions in both groups, with increased peak reflex latencies between 1.5 and 1.95 ms, but AG maintained pre-BR latencies for the MSR subjects. AG exposure did not modify balance control from pre-BR responses, but did help prevent decrements in FSR latencies post-BR.Paloski WH, Reschke MF, Feiveson AH. Bed rest and intermittent centrifugation effects on human balance and neuromotor reflexes. Aerosp Med Hum Perform. 2017; 88(9):812-818.